Heart rhythm in vitro: measuring stem cell-derived pacemaker cells on microelectrode arrays - Kussauer, Sophie; Dilk, Patrick; Elleisy, Moustafa; Michaelis, Claudia; Lichtwark, Sarina; Rimmbach, Christian; David, Robert; Jung, Julia (Frontiers in Cardiovascular Medicine, 2024)
Background: Cardiac arrhythmias have markedly increased in recent decades (1), highlighting the urgent demand for suitable test systems to evaluate the efficacy and safety of new pharmaceuticals and potential side effects of established drugs.The Microelectrode Array (MEA) system may be a suitable option, as it provides both real-time and non-invasive monitoring of cellular networks of spontaneously active cells. However, there is currently no commercially available cell source for applying this technology in the context of the cardiac conduction system (CCS). In response to this problem, our group has previously developed a protocol for the generation of pure functional cardiac pacemaker cells from mouse embryonic stem cells (ESCs). Furthermore, we compare the hanging drop method, which was previously utilized, with spherical plate-derived embryoid bodies (EBs) and the pacemaker cells that are differentiated from these.Results: We describe the application of these pacemaker cells on the MEA platform, which required a number of crucial optimization steps in terms of coating, dissociation and cell density. As a result, we were able to generate a monolayer of pure pacemaker cells on an MEA surface that is viable and electromechanically active for weeks. Furthermore, we introduced spherical plates as a convenient and expandable method to be applied during the production of induced sinoatrial bodies.We provide a tool for transferring modelling and analysis of cardiac rhythm diseases to the cell culture dish. Our system enables answering CCS-related queries within a cellular network, both in baseline conditions and post-drug exposure in a reliable and affordable manner. Ultimately, our approach could provide valuable guidance not only for cardiac pacemaker cells, but also for the generation of an MEA test platform using other sensitive nonproliferating cell types.